Shapiro like steps reveals molecular nanomagnets’ spin dynamics - Babak Abdollahipour; Jahanfar Abouie; Navid Ebrahimi (AIP Advances, 2015)
We present an accurate way to detect spin dynamics of a nutating molecular nanomagnet by inserting it in a tunnel Josephson junction and studying the current voltage (I-V) characteristic. The spin nutation of the molecular nanomagnet is generated by applying two circularly polarized magnetic fields. We demonstrate that modulation of the Josephson current by the nutation of the molecular nanomagnet’s spin appears as a stepwise structure like Shapiro steps in the I-V characteristic of the junction. Width and heights of these Shapiro-like steps are determined by two parameters of the spin nutation, frequency and amplitude of the nutation, which are simply tuned by the applied magnetic fields.